Can we modify maximal speed running posture? Implications for performance and hamstring injuries management - Mendiguchia, J.; Castana-Zambudio, A.; Jiminez-Reyes, P.; Morin, J.-B.; Edouard, P.; Conceicao, F.; Colyer, S. (International Journal of Sports Physiology and Performance, 2021)
Hamstring strain injuries are the most prevalent muscle injuries in track and field (TF). These injuries often cause prolonged symptoms and a high risk of re-injury. Strengthening of the hamstring muscles has been recommended for injury prevention. The authors review the possible role of eccentric training in TF hamstring injury prevention and introduce exercise classification criteria to guide clinicians in designing strengthening programmes adapted to TF. The principles exposed may serve as a foundation for future development and application of new eccentric programmes to decrease the high incidence of this type of injury in other sports.